Subtidal Rocky Shore Communities of the Azores: Developing a Biotope Survey Method - Wallenstein, Francisco (2008)
At 23 sites selected randomly around the island of S o Miguel (Azores), video records were made at the depths of 5, 10, 15, 20, 25, and 30 m where a rocky substratum was present. Semiquantitative abundance data of the most common benthic organisms (algae and fixed/sedentary macroinvertebrates) were recorded in the vicinity of each depth reference point. Qualitative samples of the more conspicuous organisms were taken for confirmation of identification in the laboratory. At each site, substratum type, geographical orientation, and depth level were recorded. Multivariate analysis (nonmetric multidimensional scaling; analysis of similarity Anosim tests; similarity percentages Simper analysis) on the collected data enabled patterns of community distribution to be identified, as well as their relationship to abiotic factors. Since depth was found to be the sole determining factor for communities, it was the only one considered in the subtidal biotope survey protocol proposed here.